PENGARUH KAPITALISME DAN LIBERALISME KEHIDUPAN PERKOTAAN SEBAGAI TEORI APLIKASI METODE WUJUD BERARSITEKTUR REMMENT KOOLHAAS - Burhanuddin, Burhanuddin (MEKTEK, 2010)
Remment Koolhaas, a theorist, urbanist, critics and architects of the Dutch, often talk about cultural change in urban communities. The influence of capitalism and liberalism to the urban life implicitly targeted design ideas and criticism, through his many works, a satire on urban life itself. Koolhaas called as a cynical. Work does not stop at just writing. Koolhaas in the architecture as "content" that terkamuflasekan, remains as a satire on the lives of people of the city own..